A self-healing medical magnesium alloy composite coating and preparation method thereof
Through two -step hydrophilic reaction method to prepare self -healing medical magnesium alloy composite coating, solve the problem of damage and unsatisfactory coating thickness in acidic environments in the existing technology, and realize the high of magnesium alloy high. Retain resistance and self -healing ability.
Patent Information
- Application Number
- CN202411259887.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-09-10
AI Technical Summary
In the prior art, the preparation of magnesium alloy corrosion-resistant coatings by hydrothermal method has problems such as the acidic environment to damage the magnesium alloy substrate and the coating thickness is not ideal, resulting in limited corrosion resistance effect.
The medical magnesium alloy composite coating with two -step water thermal reaction method is prepared for self -healing. First, the dense bottom coating is formed through the first water thermal reaction, and then the surface of the phosphorus limestone is formed by the second water thermal reaction to form the second water thermal reaction. Painting to ensure the density and self -healing ability of the coating.
The effect of self -healing in the PBS buffer solution is achieved, maintaining the corrosion resistance of magnesium alloy, and promoting bone development and healing through coating of the main ingredients of the bone, reducing the corrosion resistance requirements of magnesium alloy products.
Smart Images

Figure CN118773595B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biomedical materials and relates to a medical magnesium alloy coating, in particular to a self-healing medical magnesium alloy composite coating and a preparation method thereof. Background Art
[0002] The density and Young's modulus of magnesium alloy are closest to those of human bones. In addition, magnesium is an essential mineral for the human body and plays an important role in the metabolism process. Its degradation products are non-toxic to the human body and can be excreted through body fluids. Therefore, magnesium alloys have broad application prospects in the medical field and have good biocompatibility and metabolic mechanisms. However, magnesium alloys have poor corrosion resistance and rapid degradation as the bulk properties of the material, which also limits the application range of the material. Although the corrosion resistance of magnesium alloys is continuously improved through alloying, controlling impurity content, and improving processing technology capabilities, the room for improvement is limited and it still cannot be directly applied in many scenarios.
[0003] Medical magnesium alloy materials can improve their corrosion resistance through surface modification technology, thereby overcoming a series of problems caused by their rapid degradation rate. The main ways to improve the corrosion resistance of magnesium alloys are alloying, amorphization, plastic deformation and surface modification. Surface modification is one of the effective means to improve the corrosion resistance of magnesium alloys, including anodizing, micro-arc oxidation, ion implantation and surface coating. Preparing a coating on the surface of magnesium alloys is currently the most commonly used method to improve the corrosion resistance of magnesium alloys. In corrosive media, the coating can effectively improve the corrosion resistance of magnesium alloys.
[0004] Bioactive coatings such as calcium-phosphorus coatings have shown good development prospects due to their good biocompatibility and bone induction. The coating is non-toxic, pollution-free and environmentally friendly. The hydrothermal method for preparing calcium-phosphorus coatings is one of the commonly used methods. In the prior art, the hydrothermal method for preparing magnesium alloy corrosion-resistant coatings generally has the following two problems or shortcomings: First, in the hydrothermal reaction system, the pH value is generally acidic, and the acidic environment will inevitably cause a certain degree of damage to the magnesium alloy substrate; second, the obtained coating thickness is not very ideal, and the corrosion resistance effect is limited.
[0005] CN 107699885A discloses a method for preparing a magnesium hydroxide-calcium-phosphorus composite coating of a magnesium-magnesium alloy. The patent mainly discloses that a precursor solution is prepared using glucose, calcium nitrate, potassium dihydrogen phosphate, sodium hydroxide and distilled water as raw materials, and the pH of the precursor solution is adjusted to 9.98-10.20 with a strong base; then, the magnesium or magnesium alloy substrate to be treated is placed in a hydrothermal reactor, the precursor solution is poured in, and a pure magnesium or magnesium alloy surface composite coating with a thickness of 18-45 μm is prepared by a hydrothermal method, and the obtained coating presents a crystalline microstructure. The patent changes the acidic environment of the bed and obtains a corrosion-resistant magnesium alloy coating, but the coating does not have a self-healing function and cannot inhibit the degradation of the magnesium alloy.
[0006] In summary, it is necessary to provide a coating that has good biocompatibility, is completely degradable, and can effectively inhibit the degradation of magnesium alloys. Summary of the invention
[0007] In view of the deficiencies of the prior art, the purpose of the present invention is to provide a self-healing medical magnesium alloy composite coating and a preparation method thereof. If the composite coating is damaged during use, it can continue to recrystallize and assemble in a PBS buffer solution to achieve a self-healing effect and maintain the corrosion resistance of the magnesium alloy; and the components of the composite coating are the main components of bones, which can further promote bone development and growth, rapid bone healing, and reduce the corrosion resistance requirements of magnesium alloy products to a certain extent.
[0008] To achieve this object, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a method for preparing a self-healing medical magnesium alloy composite coating, the preparation method comprising the following steps:
[0010] (1) After surface treatment, the medical magnesium alloy substrate is suspended in a reaction container filled with purified water, and then sealed and subjected to a first hydrothermal reaction to obtain a bottom coating;
[0011] (2) mixing the alkali solution and the calcium phosphate aqueous solution to obtain a hydrothermal reaction solution;
[0012] Immersing the medical magnesium alloy substrate with the bottom coating in a hydrothermal reaction solution to perform a second hydrothermal reaction, and obtaining a surface coating after cooling;
[0013] (3) cleaning and drying the medical magnesium alloy substrate with the bottom coating and the surface coating to obtain the self-healing medical magnesium alloy composite coating;
[0014] The calcium-phosphate aqueous solution includes a first calcium-phosphate aqueous solution or a second calcium-phosphate aqueous solution.
[0015] The present invention uses a medical magnesium alloy as a substrate, firstly prepares a layer of chemically converted and dense coating as a bottom coating through a first hydrothermal reaction, and then prepares an apatite coating (surface coating) on the basis of the bottom coating through a second hydrothermal reaction to form a composite coating with the bottom coating. The composite coating has good biocompatibility and can be completely degraded. The crystallization mode of the surface coating is changed through process control to form a dense coating. Even if the surface coating is damaged during use, the coating crystals that fall around it can still be recrystallized and self-assembled for repair in a PBS buffer solution (an inorganic salt component close to that of human tissue fluid), thereby continuously and effectively inhibiting the degradation of the magnesium alloy and improving the corrosion resistance of the magnesium alloy.
[0016] In addition, the composite coating provided by the present invention has good coating integrity and good corrosion resistance after being screwed in and out of a grade 40 polyurethane material for three consecutive times; and the composite coating is dense and degradable, providing a barrier to corrosion of the magnesium alloy substrate.
[0017] Preferably, the immersion in step (2) includes hanging immersion.
[0018] The use of suspended immersion can maximize the surface of the medical magnesium alloy substrate, evenly contact the calcium-phosphorus aqueous solution, and obtain a more uniform coating.
[0019] As a preferred technical solution of the present invention, the medical magnesium alloy matrix in step (1) includes any one of AE series alloys, AS series alloys, WE series alloys, AZ series alloys, AM series alloys, ZK series alloys, ZM series alloys, Mg-Li series alloys, and Mg-Ca series alloys, preferably a magnesium-zinc-manganese series magnesium alloy.
[0020] Preferably, the Mg content in the medical magnesium alloy matrix in step (1) is ≥ 97%, for example, it can be 97%, 97.5%, 98%, 98.5% or 99%, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0021] As a preferred technical solution of the present invention, the surface treatment in step (1) includes physical grinding, cleaning and electrochemical polishing performed in sequence.
[0022] The purpose of the surface treatment in step (1) of the present invention is to remove lipid pollutants and the oxide film layer on the surface of the medical magnesium alloy.
[0023] Preferably, in step (1), the distance between the medical magnesium alloy substrate and the surface of purified water is 15-20 mm, for example, 15 mm, 16 mm, 17 mm, 18 mm, 19 mm or 20 mm, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0024] Preferably, the temperature of the first hydrothermal reaction in step (1) is 140-200°C, for example, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C or 200°C, but is not limited to the listed values, and other values within the numerical range not listed are also applicable.
[0025] Preferably, the pressure of the first hydrothermal reaction in step (1) is 1.6-2.0 MPa, for example, 1.6 MPa, 1.7 MPa, 1.8 MPa, 1.9 MPa or 2.0 MPa, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0026] Preferably, the time of the first hydrothermal reaction in step (1) is 2 to 5 h, for example, 2 h, 2.4 h, 2.8 h, 3.0 h, 3.6 h, 4 h, 4.4 h, 4.8 h or 5 h, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0027] Preferably, the amount of purified water added in step (1) is 20-40% of the volume of the reaction container, for example, 20%, 24%, 28%, 32%, 36% or 40%, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0028] In the present invention, the preparation method of the bottom coating is not to immerse the magnesium alloy substrate in water for reaction, but to react the magnesium alloy substrate with high-temperature and high-pressure water vapor. Compared with the immersion hydrothermal reaction, the coating obtained by the method provided by the present invention has a stronger bonding force with the substrate, the coating is more uniform, and the corrosion behavior of the magnesium alloy substrate is avoided during the preparation process;
[0029] Furthermore, the content of metallic magnesium in the medical magnesium alloy used in the present invention is relatively high (≥97%), so that the components of the obtained bottom coating include magnesium hydroxide and magnesium oxide, and other metal compounds are very small in size and are coated by the generated magnesium hydroxide and magnesium oxide coatings, so that it has excellent biocompatibility, bonding strength and corrosion resistance, laying a foundation for the subsequent preparation of surface coatings and further improving the performance of the composite coating.
[0030] As a preferred technical solution of the present invention, the raw materials for preparing the first calcium-phosphorus aqueous solution include: calcium nitrate tetrahydrate, potassium dihydrogen phosphate, tricalcium phosphate, hydrogen peroxide, a first chelating agent and purified water.
[0031] Preferably, the first chelating agent comprises any one or a combination of at least two of ethylenediaminetetraacetic acid disodium salt, D-anhydrous glucose or L-cysteine, and typical but non-limiting combinations include: a combination of ethylenediaminetetraacetic acid disodium salt and D-anhydrous glucose, a combination of ethylenediaminetetraacetic acid disodium salt and L-cysteine, a combination of D-anhydrous glucose and L-cysteine, or a combination of ethylenediaminetetraacetic acid disodium salt, D-anhydrous glucose and L-cysteine.
[0032] Preferably, the concentration of calcium nitrate tetrahydrate in the first calcium-phosphate aqueous solution is 20-80 g / L, for example, 20 g / L, 30 g / L, 40 g / L, 50 g / L, 60 g / L, 70 g / L or 80 g / L, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0033] Preferably, the concentration of potassium dihydrogen phosphate in the first calcium-phosphate aqueous solution is 5-35 g / L, for example, it can be 5 g / L, 10 g / L, 15 g / L, 20 g / L, 25 g / L, 30 g / L or 35 g / L, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0034] Preferably, the concentration of tricalcium phosphate in the first calcium-phosphate aqueous solution is 3-15 g / L, for example, 3 g / L, 5 g / L, 7 g / L, 9 g / L, 11 g / L, 13 g / L or 15 g / L, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0035] Preferably, the concentration of hydrogen peroxide in the first calcium phosphate aqueous solution is 50-80 mL / L, for example, 50 mL / L, 60 mL / L, 70 mL / L or 80 mL / L, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0036] Preferably, the concentration of disodium ethylenediaminetetraacetic acid in the first calcium-phosphate aqueous solution is 25-50 g / L, for example, it can be 20 g / L, 25 g / L, 30 g / L, 35 g / L, 40 g / L, 45 g / L or 50 g / L, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0037] Preferably, the concentration of D-anhydrous glucose in the first calcium phosphate aqueous solution is 25-50 g / L, for example, it can be 20 g / L, 25 g / L, 30 g / L, 35 g / L, 40 g / L, 45 g / L or 50 g / L, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0038] Preferably, the concentration of L-cysteine in the first calcium-phosphate aqueous solution is 20-30 g / L, for example, it can be 20 g / L, 22 g / L, 24 g / L, 26 g / L, 28 g / L or 30 g / L, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0039] Preferably, the molar ratio of calcium to phosphorus in the first calcium-phosphate aqueous solution is 1.3-1.9:1, for example, 1.3:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1 or 1.9:1, but is not limited to the listed values, and other values not listed within the numerical range are also applicable, preferably 1.5-1.8:1, and more preferably 1.6-1.7:1.
[0040] As a preferred technical solution of the present invention, the raw materials for preparing the second calcium-phosphorus aqueous solution include: calcium nitrate tetrahydrate, disodium hydrogen phosphate dodecahydrate, tricalcium phosphate, hydrogen peroxide, a second chelating agent and purified water.
[0041] Preferably, the second chelating agent comprises D-anhydrous glucose and / or L-cysteine.
[0042] Preferably, the concentration of calcium nitrate tetrahydrate in the second calcium-phosphate aqueous solution is 10-40 g / L, for example, 10 g / L, 15 g / L, 20 g / L, 25 g / L, 30 g / L, 35 g / L or 40 g / L, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0043] Preferably, the concentration of disodium hydrogen phosphate dodecahydrate in the second calcium-phosphate aqueous solution is 10-50 g / L, for example, it can be 10 g / L, 15 g / L, 20 g / L, 25 g / L, 30 g / L, 35 g / L, 40 g / L, 45 g / L or 50 g / L, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0044] Preferably, the concentration of tricalcium phosphate in the second calcium-phosphate aqueous solution is 10-40 g / L, for example, it can be 10 g / L, 15 g / L, 20 g / L, 25 g / L, 30 g / L, 35 g / L or 40 g / L, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0045] Preferably, the concentration of hydrogen peroxide in the second calcium phosphate aqueous solution is 50-80 mL / L, for example, 50 mL / L, 60 mL / L, 70 mL / L or 80 mL / L, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0046] Preferably, the concentration of D-anhydrous glucose in the second calcium phosphate aqueous solution is 15-20 g / L, for example, it can be 15 g / L, 17 g / L, 19 g / L, 21 g / L, 23 g / L or 25 g / L, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0047] Preferably, the concentration of L-cysteine in the second calcium-phosphate aqueous solution is 20-30 g / L, for example, it can be 20 g / L, 22 g / L, 24 g / L, 26 g / L, 28 g / L or 30 g / L, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0048] Preferably, the molar ratio of calcium to phosphorus in the second calcium-phosphate aqueous solution is 1.3-1.9:1, for example, 1.3:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1 or 1.9:1, but is not limited to the listed values, and other values not listed within the numerical range are also applicable, preferably 1.5-1.8:1, and more preferably 1.6-1.7:1.
[0049] In the present invention, the addition amount of various reagents in the calcium-phosphorus aqueous solution has a great influence on the ratio of calcium and phosphorus elements. The ratio of calcium and phosphorus elements will affect the crystallization mode and direction during the coating preparation process, thereby affecting the coating quality.
[0050] It is worth noting that although the compositions of the first calcium-phosphate aqueous solution and the second calcium-phosphate aqueous solution are different, the bottom coating used in the two is the same, and the process method and process parameters adopted in the preparation of the surface coating (calcium-phosphate coating) are also the same. Therefore, the changes in the process parameters and the molar ratio of calcium and phosphorus elements in the preparation of the surface coating have the same influence on the quality of the coating prepared by using the first calcium-phosphate aqueous solution or the second calcium-phosphate aqueous solution.
[0051] As a preferred technical solution of the present invention, the alkali solution in step (2) includes sodium hydroxide.
[0052] Preferably, the pH value of the hydrothermal reaction solution in step (2) is 8-12, for example, 8, 9, 10, 11 or 12, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0053] In the present invention, the pH value of the hydrothermal reaction solution will affect the quality of the coating. If the pH value is too high, the crystallization rate in the preparation process of the surface coating will be reduced, the degradation mode will tend to be more granular crystals, the porosity of the coating will increase, and the pore size will increase, thereby reducing the corrosion resistance and bonding strength of the surface coating; if the pH value is too low, the bottom coating will be corroded, thereby reducing the corrosion resistance of the composite coating.
[0054] As a preferred technical solution of the present invention, the temperature of the second hydrothermal reaction in step (2) is 80-120°C, for example, 80°C, 90°C, 100°C, 110°C or 120°C, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0055] In the present invention, the temperature of the second hydrothermal reaction mainly affects the efficiency and mode of crystallization during the preparation of the surface coating. If the temperature is too low, the crystallization mode is oriented to be flake and needle-shaped, but the efficiency is low and the crystallization quality is poor. If the temperature is too high, the crystallization efficiency is high, the crystallization mode is oriented to be granular, the porosity of the coating increases, the pore size increases, and the corrosion resistance of the coating cannot be improved.
[0056] Preferably, the pressure of the second hydrothermal reaction in step (2) is 1.0-1.5 MPa, for example, 1.0 MPa, 1.1 MPa, 1.2 MPa, 1.3 MPa, 1.4 MPa or 1.5 MPa, but is not limited to the listed values, and other values within the numerical range not listed are also applicable.
[0057] In the present invention, the pressure of the second hydrothermal reaction mainly affects the morphology of crystals during the preparation of the surface coating. If the reaction pressure is too low, the crystals grow in a diffuse manner during the reaction, which is highly random and results in poor coating quality. If the reaction pressure is too high, the crystals grow vertically to the surface of the substrate during the reaction, resulting in uneven coverage and uneven coating thickness, which produces voids and reduces the corrosion resistance of the coating.
[0058] Preferably, the time of the second hydrothermal reaction in step (2) is 3 to 6 hours, for example, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours or 6 hours, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0059] In the present invention, the time of the second hydrothermal reaction needs to be adjusted in combination with temperature and pressure, which mainly affects the thickness of the coating. When the reaction time is too short, the surface coating cannot completely cover the bottom coating or the surface coating is too thin, or the uniform modification is poor, which makes the corrosion resistance of the coating worse; if the reaction time is too long, the surface coating will be too thick, and under the action of external force, its bonding strength will decrease, making it easy to break, thereby reducing the corrosion resistance.
[0060] The present invention adjusts the temperature, pressure and time of the second hydrothermal reaction so that crystals grow in flake and needle shapes during the reaction, thereby obtaining a surface coating with good density and hydroxyapatite as the main component. The surface coating has unique similarities with the minerals found in natural bones, can promote remineralization and stimulate bone growth, and is a key factor in effective bone regeneration.
[0061] As a preferred technical solution of the present invention, the cleaning treatment in step (3) includes water washing.
[0062] Preferably, the drying temperature in step (3) is 40-60°C, for example, 40°C, 44°C, 48°C, 52°C, 56°C or 60°C, but is not limited to the listed values, and other values within the numerical range not listed are also applicable.
[0063] Preferably, the drying time in step (3) is 15 to 60 min, for example, 15 min, 20 min, 30 min, 40 min, 50 min or 60 min, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0064] In the present invention, the purpose of the drying is to dry and solidify the surface coating; if the temperature during the drying process is too high, the crystals of the coating will be rearranged, thereby affecting the quality of the coating; if the drying temperature is too low, the drying and solidification effect of the coating will be poor, resulting in gaps left after solvent residues are dried in the coating, thereby affecting the quality of the coating.
[0065] It is worth noting that the present invention effectively avoids damage to the bottom coating during the preparation of the surface coating by reasonably selecting the composition of the calcium-phosphate aqueous solution and the process parameters of the second hydrothermal reaction, thereby achieving a synergistic effect between the bottom coating and the surface coating. The resulting composite coating achieves higher corrosion resistance and a more excellent process-controlled crystal growth mode, making the coating more durable.
[0066] As a preferred technical solution of the present invention, the preparation method of the self-healing medical magnesium alloy composite coating provided in the first aspect of the present invention comprises the following steps:
[0067] (1) The medical magnesium alloy substrate is physically polished, cleaned and electrochemically polished in sequence, and then suspended in a reaction container filled with purified water. After being sealed, a first hydrothermal reaction is performed at a temperature of 140-200° C. and a pressure of 1.6-2.0 MPa for 2-5 h to obtain a bottom coating;
[0068] The distance between the medical magnesium alloy substrate and the surface of purified water is 15-20 mm;
[0069] (2) mixing sodium hydroxide and calcium phosphate aqueous solution to obtain a hydrothermal reaction solution with a pH value of 8 to 12;
[0070] The medical magnesium alloy substrate with the bottom coating is immersed in a hydrothermal reaction solution at a temperature of 80 to 120° C. and a pressure of 1.0 to 1.5 MPa for a second hydrothermal reaction for 3 to 6 hours, and a surface coating is obtained after cooling;
[0071] (3) washing the medical magnesium alloy substrate with the bottom coating and the surface coating with water, and then drying at a temperature of 40 to 60° C. for 15 to 60 minutes to obtain the self-healing medical magnesium alloy composite coating;
[0072] The calcium-phosphate aqueous solution includes a first calcium-phosphate aqueous solution or a second calcium-phosphate aqueous solution.
[0073] In a second aspect, the present invention provides a self-healing medical magnesium alloy composite coating, wherein the self-healing medical magnesium alloy composite coating is obtained by the preparation method provided in the first aspect.
[0074] From the surface of the medical magnesium alloy substrate to the outside, the composite coating includes a bottom coating and a surface coating that are stacked.
[0075] The present invention further improves the corrosion resistance and bonding strength of the coating by arranging a stacked bottom coating and a surface coating on the surface of the medical magnesium alloy bone plate or bone screw; more specifically, under the condition of a large friction force formed by twisting and screwing the bone screw, the bottom coating still maintains good integrity, and even if the surface coating is broken, it still adheres to the surface of the bottom coating, which significantly improves the corrosion resistance;
[0076] In addition, even if the composite coating of the present invention is damaged during use, it can still continue to recrystallize and assemble in the tissue solution to achieve a self-healing effect and maintain the corrosion resistance of the sample. Moreover, the surface coating is the main component of bones, which can further promote bone development and growth and rapid bone healing, thereby reducing the corrosion resistance requirements of magnesium alloy products to a certain extent.
[0077] As a preferred technical solution of the present invention, the components of the bottom coating include magnesium hydroxide and magnesium oxide.
[0078] Preferably, the thickness of the bottom coating is 8-15 μm, for example, 8 μm, 10 μm, 12 μm, 14 μm or 15 μm, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0079] Preferably, the composition of the surface coating includes hydroxyapatite.
[0080] Preferably, the thickness of the composite coating is 50-80 μm, for example, 50 μm, 60 μm, 70 μm or 80 μm, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0081] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0082] Compared with the prior art, the present invention has the following beneficial effects:
[0083] (1) The self-healing medical magnesium alloy composite coating provided by the present invention comprises a bottom coating and a surface coating which are stacked. The composite coating has good compactness and biocompatibility, is completely degradable, and can effectively inhibit the degradation of magnesium alloys, improve the corrosion resistance of magnesium alloys, and has a strong bonding force with the medical magnesium alloy substrate. After being screwed in and out of a 40-grade polyurethane block three times, the coating still maintains good coating integrity;
[0084] (2) The self-healing medical magnesium alloy composite coating provided by the present invention has self-healing properties. Even if the surface coating is damaged during use, the coating crystals that fall around it can still recrystallize and self-assemble to repair in the tissue solution, continuously and effectively inhibiting the degradation of the magnesium alloy and improving the corrosion resistance of the magnesium alloy.
[0085] (3) The main component of the surface coating in the self-healing medical magnesium alloy composite coating provided by the present invention is apatite, which has a unique similarity to the minerals found in natural bones, can promote remineralization and stimulate bone growth, and is a key factor in effective bone regeneration;
[0086] (4) The surface coating of the self-healing medical magnesium alloy composite coating provided by the present invention is dense, which is different from the porous calcium-phosphorus coating prepared by the traditional process, and the composite coating is degradable. The composite coating formed under high temperature and high pressure environment provides a barrier to corrosion of the magnesium alloy substrate. BRIEF DESCRIPTION OF THE DRAWINGS
[0087] Figure 1 This is a scanning electron microscope image of the self-healing medical magnesium alloy composite coating provided in Example 1 of the present invention, with a scale of 20 μm;
[0088] Figure 2 This is a scanning electron microscope image of the self-healing medical magnesium alloy composite coating provided in Example 1 of the present invention, with a scale of 100 μm;
[0089] Figure 3 This is a scanning electron microscope image of the self-healing medical magnesium alloy composite coating provided in Example 1 of the present invention after the bonding strength test, with a scale of 500 μm;
[0090] Figure 4 This is a scanning electron microscope image of the self-healing medical magnesium alloy composite coating provided in Example 2 of the present invention after the bonding strength test, with a scale of 500 μm;
[0091] Figure 5 This is a scanning electron microscope image of the self-healing medical magnesium alloy composite coating provided in Comparative Example 1 of the present invention after the bonding strength test, with a scale of 500 μm;
[0092] Figure 6 This is a comparison chart of corrosion resistance test results of the bottom coating provided in Example 1 of the present invention and the self-healing medical magnesium alloy composite coating after the bonding strength test;
[0093] Figure 7 This is a comparison chart of corrosion resistance test results of the bottom coating and the self-healing medical magnesium alloy composite coating provided in Example 2 of the present invention after the bonding strength test;
[0094] Figure 8 It is a comparison chart of the corrosion resistance test results of the bottom coating and the self-healing medical magnesium alloy composite coating provided in Comparative Example 1 of the present invention after the bonding strength test;
[0095] Fig. 9 This is a comparison chart of the corrosion resistance test results of the self-healing medical magnesium alloy composite coating before and after self-healing provided in Example 1 of the present invention;
[0096] FIG10( a ) is a light microscope image of the self-healing medical magnesium alloy composite coating provided in Example 1 of the present invention before being destroyed;
[0097] FIG10( b ) is a light microscope picture of the self-healing medical magnesium alloy composite coating provided in Example 1 of the present invention after being damaged;
[0098] FIG10( c ) is an optical microscope image of the self-healing medical magnesium alloy composite coating provided in Example 1 of the present invention after self-healing. DETAILED DESCRIPTION
[0099] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0100] Example 1
[0101] This embodiment provides a self-healing medical magnesium alloy composite coating. From the surface of the medical magnesium alloy substrate to the outside, the composite coating includes a bottom coating and a surface coating that are stacked.
[0102] The bottom coating is composed of a mixture of magnesium hydroxide and magnesium oxide; the bottom coating has a thickness of 10 μm; and the composite coating has a thickness of 60 μm.
[0103] The method for preparing the self-healing medical magnesium alloy composite coating provided in this embodiment comprises the following steps:
[0104] (1) The medical magnesium-zinc-manganese alloy substrate is physically polished, cleaned and electrochemically polished in sequence, and then suspended in a reaction container filled with purified water. After being sealed, a first hydrothermal reaction is performed at a temperature of 160° C. and a pressure of 1.8 MPa for 3 h to obtain a bottom coating;
[0105] The distance between the medical magnesium alloy substrate and the surface of purified water is 18 mm;
[0106] (2) mixing sodium hydroxide and the first calcium phosphate aqueous solution to obtain a hydrothermal reaction solution with a pH value of 12;
[0107] The medical magnesium alloy substrate with the bottom coating is suspended and immersed in a hydrothermal reaction solution at a temperature of 98° C. and a pressure of 1.2 MPa for 4 hours for a second hydrothermal reaction, and a surface coating is obtained after cooling;
[0108] In the first calcium-phosphate aqueous solution, the concentration of calcium nitrate tetrahydrate is 39.44 g / L, the concentration of potassium dihydrogen phosphate is 13.60 g / L, the concentration of tricalcium phosphate is 6.72 g / L, the concentration of hydrogen peroxide is 68 mL / L, the concentration of ethylenediaminetetraacetic acid disodium salt is 37.22 g / L, and the concentration of D-anhydrous glucose is 36.03 g / L;
[0109] The molar ratio of calcium to phosphorus in the first calcium-phosphorus aqueous solution is 1.6:1;
[0110] (3) The medical magnesium alloy substrate with the bottom coating and the surface coating is washed with water, and then dried at 50° C. for 30 minutes to obtain the self-healing medical magnesium alloy composite coating.
[0111] The scanning electron microscope image of the self-healing medical magnesium alloy composite coating provided in this embodiment at a scale of 20 μm is as follows: Figure 1 The SEM images at 100 μm are shown in Figure 2 shown.
[0112] according to Figure 1 and Figure 2 It can be seen that the self-healing medical magnesium alloy composite coating provided in this embodiment has a microstructure of flaky and needle-shaped crystals.
[0113] Example 2
[0114] This embodiment provides a self-healing medical magnesium alloy composite coating. From the surface of the medical magnesium alloy substrate to the outside, the composite coating includes a bottom coating and a surface coating that are stacked.
[0115] The bottom coating is composed of a mixture of magnesium hydroxide and magnesium oxide, and the thickness of the bottom coating is 10 μm; the thickness of the composite coating is 55 μm.
[0116] The method for preparing the self-healing medical magnesium alloy composite coating provided in this embodiment comprises the following steps:
[0117] (1) The medical magnesium-zinc-manganese alloy substrate is physically polished, cleaned and electrochemically polished in sequence, and then suspended in a reaction container filled with purified water. After being sealed, a first hydrothermal reaction is performed at a temperature of 160° C. and a pressure of 1.8 MPa for 3 h to obtain a bottom coating;
[0118] The distance between the medical magnesium alloy substrate and the surface of purified water is 18 mm;
[0119] (2) mixing sodium hydroxide and a second calcium phosphate aqueous solution to obtain a hydrothermal reaction solution with a pH value of 9;
[0120] The medical magnesium alloy substrate with the bottom coating is suspended and immersed in a hydrothermal reaction solution at a temperature of 120° C. and a pressure of 1.2 MPa for 3 hours for a second hydrothermal reaction, and a surface coating is obtained after cooling;
[0121] The concentration of calcium nitrate tetrahydrate in the second calcium-phosphate aqueous solution is 23.61 g / L, the concentration of disodium hydrogen phosphate dodecahydrate is 17.91 g / L, the concentration of tricalcium phosphate is 20.78 g / L, the concentration of hydrogen peroxide is 68 mL / L, the concentration of D-anhydrous glucose is 18.02 g / L, and the concentration of L-cysteine is 24.33 g / L;
[0122] The molar ratio of calcium to phosphorus in the second calcium-phosphorus aqueous solution is 1.6:1;
[0123] (3) The medical magnesium alloy substrate with the bottom coating and the surface coating is washed with water, and then dried at 50° C. for 30 minutes to obtain the self-healing medical magnesium alloy composite coating.
[0124] Example 3
[0125] This embodiment provides a self-healing medical magnesium alloy composite coating. From the surface of the medical magnesium alloy substrate to the outside, the composite coating includes a bottom coating and a surface coating that are stacked.
[0126] The bottom coating is composed of a mixture of magnesium hydroxide and magnesium oxide; the bottom coating has a thickness of 12 μm; and the composite coating has a thickness of 70 μm.
[0127] The method for preparing the self-healing medical magnesium alloy composite coating provided in this embodiment comprises the following steps:
[0128] (1) The medical ZM series magnesium alloy substrate was physically polished, cleaned and electrochemically polished in sequence, and then suspended in a reaction container filled with purified water. After sealing, the substrate was subjected to a first hydrothermal reaction at a temperature of 160° C. and a pressure of 1.6 MPa for 4 h to obtain a bottom coating;
[0129] The distance between the medical magnesium alloy substrate and the surface of purified water is 15 mm;
[0130] (2) mixing sodium hydroxide and a second calcium phosphate aqueous solution to obtain a hydrothermal reaction solution with a pH value of 8;
[0131] The medical magnesium alloy substrate with the bottom coating is suspended and immersed in a hydrothermal reaction solution at a temperature of 80° C. and a pressure of 1.5 MPa for 6 hours for a second hydrothermal reaction, and a surface coating is obtained after cooling;
[0132] The concentration of calcium nitrate tetrahydrate in the second calcium-phosphate aqueous solution is 15 g / L, the concentration of disodium hydrogen phosphate dodecahydrate is 15 g / L, the concentration of tricalcium phosphate is 15 g / L, the concentration of hydrogen peroxide is 50 mL / L, the concentration of D-anhydrous glucose is 15 g / L, and the concentration of L-cysteine is 20 g / L;
[0133] The molar ratio of calcium to phosphorus in the second calcium-phosphorus aqueous solution is 1.5:1;
[0134] (3) The medical magnesium alloy substrate with the bottom coating and the surface coating is washed with water, and then dried at 40° C. for 60 minutes to obtain the self-healing medical magnesium alloy composite coating.
[0135] Example 4
[0136] This embodiment provides a self-healing medical magnesium alloy composite coating. From the surface of the medical magnesium alloy substrate to the outside, the composite coating includes a bottom coating and a surface coating that are stacked.
[0137] The bottom coating is composed of a mixture of magnesium hydroxide and magnesium oxide; the bottom coating has a thickness of 10 μm; and the composite coating has a thickness of 70 μm.
[0138] The preparation method of the self-healing medical magnesium alloy composite coating provided in this embodiment is different from that in Embodiment 1 only in that:
[0139] In this embodiment, the first calcium phosphate aqueous solution described in step (2) is adjusted; the concentration of calcium nitrate tetrahydrate in the first calcium phosphate aqueous solution is 30 g / L, the concentration of potassium dihydrogen phosphate is 9 g / L, the concentration of tricalcium phosphate is 9 g / L, the concentration of hydrogen peroxide is 60 mL / L, the concentration of ethylenediaminetetraacetic acid disodium salt is 25 g / L, the concentration of D-anhydrous glucose is 50 g / L; the concentration of L-cysteine is 20 g / L;
[0140] The molar ratio of calcium to phosphorus in the first calcium-phosphorus aqueous solution is 1.7:1.
[0141] Example 5
[0142] This embodiment provides a self-healing medical magnesium alloy composite coating. From the surface of the medical magnesium alloy substrate to the outside, the composite coating includes a bottom coating and a surface coating that are stacked.
[0143] The bottom coating is composed of a mixture of magnesium hydroxide and magnesium oxide; the bottom coating has a thickness of 10 μm; and the composite coating has a thickness of 40 μm.
[0144] The preparation method of the self-healing medical magnesium alloy composite coating provided in this embodiment is different from that in Embodiment 2 only in that:
[0145] In this embodiment, the chelating agent in the second calcium phosphate aqueous solution in step (2) is adjusted to 35 g / L of disodium ethylenediaminetetraacetic acid.
[0146] Example 6
[0147] This embodiment provides a self-healing medical magnesium alloy composite coating. From the surface of the medical magnesium alloy substrate to the outside, the composite coating includes a bottom coating and a surface coating that are stacked.
[0148] The bottom coating is composed of a mixture of magnesium hydroxide and magnesium oxide; the bottom coating has a thickness of 10 μm; and the composite coating has a thickness of 55 μm.
[0149] The preparation method of the self-healing medical magnesium alloy composite coating provided in this embodiment is different from that in Embodiment 1 only in that:
[0150] In this embodiment, the temperature of the second hydrothermal reaction in step (2) is adjusted to 70°C.
[0151] Example 7
[0152] This embodiment provides a self-healing medical magnesium alloy composite coating. From the surface of the medical magnesium alloy substrate to the outside, the composite coating includes a bottom coating and a surface coating that are stacked.
[0153] The bottom coating is composed of a mixture of magnesium hydroxide and magnesium oxide; the bottom coating has a thickness of 10 μm; and the composite coating has a thickness of 90 μm.
[0154] The preparation method of the self-healing medical magnesium alloy composite coating provided in this embodiment is different from that in Embodiment 1 only in that:
[0155] In this embodiment, the temperature of the second hydrothermal reaction in step (2) is adjusted to 140°C.
[0156] Example 8
[0157] This embodiment provides a self-healing medical magnesium alloy composite coating. From the surface of the medical magnesium alloy substrate to the outside, the composite coating includes a bottom coating and a surface coating that are stacked.
[0158] The bottom coating is composed of a mixture of magnesium hydroxide and magnesium oxide; the bottom coating has a thickness of 10 μm; and the composite coating has a thickness of 55 μm.
[0159] The preparation method of the self-healing medical magnesium alloy composite coating provided in this embodiment is different from that in Embodiment 1 only in that:
[0160] In this embodiment, the pressure of the second hydrothermal reaction in step (2) is adjusted to 0.8 MPa.
[0161] Example 9
[0162] This embodiment provides a self-healing medical magnesium alloy composite coating. From the surface of the medical magnesium alloy substrate to the outside, the composite coating includes a bottom coating and a surface coating that are stacked.
[0163] The bottom coating is composed of a mixture of magnesium hydroxide and magnesium oxide; the bottom coating has a thickness of 10 μm; and the composite coating has a thickness of 70 μm.
[0164] The preparation method of the self-healing medical magnesium alloy composite coating provided in this embodiment is different from that in Embodiment 1 only in that:
[0165] In this embodiment, the pressure of the second hydrothermal reaction in step (2) is adjusted to 1.8 MPa.
[0166] Example 10
[0167] This embodiment provides a self-healing medical magnesium alloy composite coating. From the surface of the medical magnesium alloy substrate to the outside, the composite coating includes a bottom coating and a surface coating that are stacked.
[0168] The bottom coating is composed of a mixture of magnesium hydroxide and magnesium oxide; the bottom coating has a thickness of 10 μm; and the composite coating has a thickness of 30 μm.
[0169] The preparation method of the self-healing medical magnesium alloy composite coating provided in this embodiment is different from that in Embodiment 1 only in that:
[0170] In this embodiment, the time of the second hydrothermal reaction in step (2) is adjusted to 2 hours.
[0171] Embodiment 11
[0172] This embodiment provides a self-healing medical magnesium alloy composite coating. From the surface of the medical magnesium alloy substrate to the outside, the composite coating includes a bottom coating and a surface coating that are stacked.
[0173] The bottom coating is a mixture of magnesium hydroxide and magnesium oxide; the thickness of the bottom coating is 10 μm; the thickness of the composite coating is 100 μm.
[0174] The preparation method of the self-healing medical magnesium alloy composite coating provided in this embodiment is different from that in Embodiment 1 only in that:
[0175] In this embodiment, the time of the second hydrothermal reaction in step (2) is adjusted to 8 hours.
[0176] Example 12
[0177] This embodiment provides a self-healing medical magnesium alloy composite coating. From the surface of the medical magnesium alloy substrate to the outside, the composite coating includes a bottom coating and a surface coating that are stacked.
[0178] The bottom coating is composed of a mixture of magnesium hydroxide and magnesium oxide; the bottom coating has a thickness of 10 μm; and the composite coating has a thickness of 60 μm.
[0179] The preparation method of the self-healing medical magnesium alloy composite coating provided in this embodiment is different from that in Embodiment 1 only in that:
[0180] In this embodiment, the drying temperature in step (3) is adjusted to 30°C.
[0181] Example 13
[0182] This embodiment provides a self-healing medical magnesium alloy composite coating. From the surface of the medical magnesium alloy substrate to the outside, the composite coating includes a bottom coating and a surface coating that are stacked.
[0183] The bottom coating is composed of a mixture of magnesium hydroxide and magnesium oxide; the bottom coating has a thickness of 10 μm; and the composite coating has a thickness of 60 μm.
[0184] The preparation method of the self-healing medical magnesium alloy composite coating provided in this embodiment is different from that in Embodiment 1 only in that:
[0185] In this embodiment, the drying temperature in step (3) is adjusted to 80°C.
[0186] Embodiment 14
[0187] This embodiment provides a self-healing medical magnesium alloy composite coating. From the surface of the medical magnesium alloy substrate to the outside, the composite coating includes a bottom coating and a surface coating that are stacked.
[0188] The bottom coating is composed of a mixture of magnesium hydroxide and magnesium oxide; the bottom coating has a thickness of 10 μm; and the composite coating has a thickness of 35 μm.
[0189] The preparation method of the self-healing medical magnesium alloy composite coating provided in this embodiment is different from that in Embodiment 1 only in that:
[0190] In this embodiment, the concentration of calcium nitrate tetrahydrate in the calcium-phosphate aqueous solution in step (2) is adjusted to 50 g / L, the concentration of potassium dihydrogen phosphate is adjusted to 32.52 g / L, and the concentration of tricalcium phosphate is adjusted to 9.00 g / L;
[0191] In this embodiment, the molar ratio of calcium to phosphorus in the first calcium-phosphorus aqueous solution is 1.0:1.
[0192] Embodiment 15
[0193] This embodiment provides a self-healing medical magnesium alloy composite coating. From the surface of the medical magnesium alloy substrate to the outside, the composite coating includes a bottom coating and a surface coating that are stacked.
[0194] The bottom coating is composed of a mixture of magnesium hydroxide and magnesium oxide; the bottom coating has a thickness of 10 μm; and the composite coating has a thickness of 85 μm.
[0195] The preparation method of the self-healing medical magnesium alloy composite coating provided in this embodiment is different from that in Embodiment 1 only in that:
[0196] In this embodiment, the concentration of calcium nitrate tetrahydrate in the calcium-phosphate aqueous solution in step (2) is adjusted to 50 g / L, the concentration of potassium dihydrogen phosphate is adjusted to 11.84 g / L, and the concentration of tricalcium phosphate is adjusted to 10.00 g / L;
[0197] In this embodiment, the molar ratio of calcium to phosphorus in the first calcium-phosphorus aqueous solution is 2.0:1.
[0198] Example 16
[0199] This embodiment provides a self-healing medical magnesium alloy composite coating. From the surface of the medical magnesium alloy substrate to the outside, the composite coating includes a bottom coating and a surface coating that are stacked.
[0200] The bottom coating comprises a mixture of magnesium hydroxide and magnesium oxide; the bottom coating has a thickness of 10 μm; and the composite coating has a thickness of 15 μm.
[0201] The preparation method of the self-healing medical magnesium alloy composite coating provided in this embodiment is different from that in Embodiment 1 only in that:
[0202] In this embodiment, the concentration of calcium nitrate tetrahydrate in the first calcium-phosphate aqueous solution in step (2) is adjusted to 7.5 g / L, the concentration of potassium dihydrogen phosphate is adjusted to 2.5 g / L, and the concentration of tricalcium phosphate is adjusted to 2.0 g / L; the molar ratio of calcium to phosphorus in the first calcium-phosphate aqueous solution is 1.6:1.
[0203] Embodiment 17
[0204] This embodiment provides a self-healing medical magnesium alloy composite coating. From the surface of the medical magnesium alloy substrate to the outside, the composite coating includes a bottom coating and a surface coating that are stacked.
[0205] The bottom coating comprises a mixture of magnesium hydroxide and magnesium oxide; the bottom coating has a thickness of 10 μm; and the composite coating has a thickness of 60 μm.
[0206] The preparation method of the self-healing medical magnesium alloy composite coating provided in this embodiment is different from that in Embodiment 1 only in that:
[0207] In this embodiment, the concentration of potassium dihydrogen phosphate in the first calcium-phosphate aqueous solution in step (2) is adjusted to 18.40 g / L; the molar ratio of calcium to phosphorus in the first calcium-phosphate aqueous solution is 1.3:1.
[0208] Embodiment 18
[0209] This embodiment provides a self-healing medical magnesium alloy composite coating. From the surface of the medical magnesium alloy substrate to the outside, the composite coating includes a bottom coating and a surface coating that are stacked.
[0210] The bottom coating is composed of a mixture of magnesium hydroxide and magnesium oxide; the bottom coating has a thickness of 10 μm; and the composite coating has a thickness of 60 μm.
[0211] The preparation method of the self-healing medical magnesium alloy composite coating provided in this embodiment is different from that in Embodiment 1 only in that:
[0212] In this embodiment, the concentration of potassium dihydrogen phosphate in the first calcium-phosphate aqueous solution in step (2) is adjusted to 15.20 g / L; the molar ratio of calcium to phosphorus in the first calcium-phosphate aqueous solution is 1.5:1.
[0213] Embodiment 19
[0214] This embodiment provides a self-healing medical magnesium alloy composite coating. From the surface of the medical magnesium alloy substrate to the outside, the composite coating includes a bottom coating and a surface coating that are stacked.
[0215] The bottom coating is composed of a mixture of magnesium hydroxide and magnesium oxide; the bottom coating has a thickness of 10 μm; and the composite coating has a thickness of 60 μm.
[0216] The preparation method of the self-healing medical magnesium alloy composite coating provided in this embodiment is different from that in Embodiment 1 only in that:
[0217] In this embodiment, the concentration of potassium dihydrogen phosphate in the first calcium-phosphate aqueous solution in step (2) is adjusted to 10.75 g / L; the molar ratio of calcium to phosphorus in the first calcium-phosphate aqueous solution is 1.9:1.
[0218] Comparative Example 1
[0219] This comparative example provides a self-healing medical magnesium alloy composite coating. From the surface of the medical magnesium alloy substrate to the outside, the composite coating includes a bottom coating and a surface coating that are stacked.
[0220] The bottom coating is composed of a mixture of magnesium hydroxide and magnesium oxide; the bottom coating has a thickness of 10 μm; and the composite coating has a thickness of 30 μm.
[0221] The preparation method of the self-healing medical magnesium alloy composite coating provided in this comparative example is different from that in Example 1 in that:
[0222] In this comparative example, the temperature of the second hydrothermal reaction in step (2) is adjusted to room temperature, the pressure is adjusted to normal pressure, and the drying process in step (3) is omitted.
[0223] Comparative Example 2
[0224] This comparative example provides a self-healing medical magnesium alloy composite coating. From the surface of the medical magnesium alloy substrate to the outside, the composite coating includes a bottom coating and a surface coating that are stacked.
[0225] The thickness of the bottom coating is 5 μm; the thickness of the composite coating is uneven.
[0226] The preparation method of the self-healing medical magnesium alloy composite coating provided in this comparative example is different from that in Example 1 in that:
[0227] In this comparative example, the suspension described in step (1) is adjusted to immersion.
[0228] Comparative Example 3
[0229] This comparative example provides a self-healing medical magnesium alloy composite coating, which includes a surface coating in a direction from the surface of the medical magnesium alloy substrate to the outside.
[0230] The surface coating has a non-uniform thickness.
[0231] The preparation method of the self-healing medical magnesium alloy composite coating provided in this comparative example is different from that in Example 1 in that:
[0232] In this comparative example, the process of preparing the bottom coating in step (1) is omitted, that is, in this comparative example, the surface coating is directly prepared on the surface of the medical magnesium alloy substrate.
[0233] Performance testing:
[0234] (1) The self-healing medical magnesium alloy composite coatings provided in the above embodiments and comparative examples were tested for bonding strength. The test method is: using a 40-grade polyurethane material (cortical bone hardness) to screw the magnesium alloy coating in and out three times. If the coating remains intact, it means that the coating has good bonding strength with the magnesium alloy substrate; if the coating is damaged, it means that the bonding strength between the coating and the magnesium alloy substrate is poor;
[0235] The bonding strength test results are shown in Table 1, wherein the scanning electron microscope images of the magnesium self-healing medical magnesium alloy composite coatings provided in Example 1, Example 2 and Comparative Example 1 after the bonding strength test are shown in Table 1. Figure 3 , Figure 4 and Figure 5 As shown;
[0236] (2) The self-healing medical magnesium alloy composite coatings provided in the above embodiments and comparative examples that have undergone the bonding strength test were subjected to a corrosion resistance test. The reagent used in the electrochemical test was a PBS solution with a pH of 7.4; the initial voltage was -0.3 V, the end voltage was 0.3 V, the time was 120 s, and the Scan Rate was 1 mV / s.
[0237] The corrosion resistance test results are shown in Table 1, wherein the corrosion resistance test results of the bottom coating and the composite coating provided in Example 1, Example 2 and Comparative Example 1 after the bonding strength test are shown in Table 1. Figure 6 , Figure 7 and Figure 8 As shown;
[0238] (3) Self-healing performance test:
[0239] The composite coating provided in Example 1 was destroyed, and then the destroyed coating was placed in a PBS solution with a pH of 7.4 for 48 hours, and then electrochemically tested after being taken out and dried. The corrosion resistance test results of the composite coating before and after self-healing are shown in the figure below. Fig. 9 As shown;
[0240] In addition, optical microscopic images of the composite coating provided in Example 1 before being destroyed, after being destroyed, and after self-healing are shown in FIG. 10 (a), FIG. 10 (b), and FIG. 10 (c), respectively.
[0241] Among them, in the performance testing process of the present invention, the coatings used are all coatings set on the surface of the self-tapping screws.
[0242] Table 1
[0243] Corrosion current (nA) Corrosion potential (V) Is the coating intact? Example 1 73.5 -1.59 yes Example 2 95.6 -1.61 yes Example 3 143.7 -1.63 yes Example 4 94.8 -1.61 yes Example 5 971.7 -1.69 no Example 6 1423.8 -1.78 no Example 7 1796.2 -1.80 no Example 8 1101.9 -1.71 no Example 9 1267.1 -1.73 no Example 10 1546.7 -1.75 no Embodiment 11 2056.4 -1.80 no Example 12 573.2 -1.73 yes Example 13 335.6 -1.70 yes Embodiment 14 2051.7 -1.81 no Embodiment 15 1085.6 -1.70 no Example 16 5210.9 -1.83 no Embodiment 17 645.3 -1.67 yes Embodiment 18 241.8 -1.64 yes Embodiment 19 687.4 -1.67 yes Comparative Example 1 28100 -1.85 no Comparative Example 2 1987.9 -1.81 no Comparative Example 3 4810.3 -1.82 no
[0244] According to the data and diagram in Table 1, we can know the following points:
[0245] (1) Comprehensive analysis of Examples 1-4 shows that the composite coating provided by the present invention has excellent corrosion resistance and bonding ability;
[0246] according to Figure 3 and Figure 4 It can be seen that the composite coating provided by the present invention still maintains good integrity after being screwed in and out of the 40-grade polyurethane material (cortical bone hardness) for three consecutive times; Figure 6 and Figure 7 It can be seen that compared with the bottom coating, the corrosion resistance of the composite coating provided by the present invention is significantly improved. Furthermore, the composite coating provided by the present invention still has excellent corrosion resistance after being screwed in and out of a 40-grade polyurethane material (cortical bone hardness) for three consecutive times.
[0247] (2) Comprehensive analysis of Example 2 and Example 5 shows that the raw materials for preparing the calcium-phosphorus aqueous solution used in the preparation process of the surface coating of the present invention will affect the quality of the coating. Selecting a reasonable calcium-phosphorus aqueous solution is more conducive to obtaining a coating with excellent performance;
[0248] (3) Comprehensive analysis of Example 1 and Examples 6-11 shows that changes in the process parameters of the second hydrothermal reaction will affect the coating quality;
[0249] When the temperature of the second hydrothermal reaction is too low (such as in Example 6), the crystallization quality during the reaction is poor, resulting in a decrease in the corrosion resistance of the composite coating; when the temperature of the second hydrothermal reaction is too high (such as in Example 7), the porosity and pore size of the resulting coating increase, resulting in a decrease in the corrosion resistance of the composite coating;
[0250] When the pressure of the second hydrothermal reaction is too low (such as in Example 8), the quality of the obtained coating is poor; when the pressure of the second hydrothermal reaction is too high (such as in Example 9), the thickness and coverage of the obtained coating are uneven, and pores are generated, resulting in a decrease in the corrosion resistance of the composite coating;
[0251] When the second hydrothermal reaction time is too short (such as in Example 10), the thickness of the obtained coating is thin and uneven, resulting in poor corrosion resistance and bonding strength of the coating; when the second hydrothermal reaction time is too long (such as in Example 11), the thickness of the obtained coating is thick, the bonding strength decreases, and the corrosion resistance of the composite coating is poor;
[0252] (4) Comprehensive analysis of Example 1 and Examples 12-13 shows that the adjustment of the drying temperature will affect the drying and curing of the surface coating. When the drying temperature is too low (such as Example 12), the residual reagent will cause pores in the coating, resulting in a decrease in the corrosion resistance of the composite coating; when the drying temperature is too high (such as Example 13), the quality of the coating will deteriorate.
[0253] (5) Comprehensive analysis of Example 1 and Examples 14-19 shows that the molar ratio of calcium to phosphorus in the calcium-phosphorus aqueous solution affects the corrosion resistance and bonding strength of the obtained coating; when the calcium-phosphorus ratio in the calcium-phosphorus aqueous solution is too high or too low, the main components of the coating obtained by the preparation method provided by the present invention are changed, thereby causing a decrease in the corrosion resistance and bonding strength of the coating;
[0254] Analysis of Example 1 and Examples 14-15 shows that, during the preparation process, even if the concentration of each component in the calcium-phosphate aqueous solution is selected appropriately, if the calcium-phosphorus molar ratio is too high or too low, the corrosion resistance and binding ability of the obtained coating will also decrease; Analysis of Example 1 and Example 16 shows that, during the preparation process, even if the calcium-phosphorus molar ratio of the calcium-phosphate aqueous solution is selected appropriately, if the concentration of each component in the calcium-phosphate aqueous solution is too low, the corrosion resistance and binding ability of the obtained coating will also decrease; It can be seen that the concentration of each component in the calcium-phosphate aqueous solution and the calcium-phosphorus molar ratio complement each other and have a synergistic effect on the performance of the obtained coating;
[0255] (6) Comprehensive analysis of Example 1 and Comparative Example 1 shows that the corrosion resistance of the composite coating provided in Comparative Example 1 is reduced;
[0256] according to Figure 3 and Figure 5 It can be seen that after the bonding test, the coating surface provided by Comparative Example 1 was obviously damaged; Figure 8 and Figure 6 It can be seen that the corrosion resistance of the composite coating provided in Comparative Example 1 has significantly decreased;
[0257] (7) Comprehensive analysis of Example 1 and Comparative Example 2 shows that when the magnesium alloy is immersed in pure water, the bottom coating obtained has poor firmness and is thin, and there is local corrosion. The surface coating prepared on the basis of the composite coating obtained has poor quality due to the unstable and poor interface of the bottom coating, uneven thickness of the surface coating, and partial falling of the surface coating. Even if the surface coating completely covers the sample, the corrosion resistance is not high.
[0258] (8) Comprehensive analysis of Example 1 and Comparative Example 3 shows that the surface coating directly disposed on the surface of the magnesium alloy has an uneven thickness and poor firmness;
[0259] (9) According to Fig. 9It can be seen that the corrosion resistance of the composite coating after self-healing is significantly higher than that of the composite coating after damage, but its corrosion resistance is slightly lower than that of the undamaged composite coating; according to Figures 10 (a), 10 (b) and 10 (c), it can be seen that after the composite coating provided by the present invention is significantly damaged, there are no obvious cracks on the coating surface after the self-healing process; this proves that the composite coating provided by the present invention has a certain self-repair and self-healing ability.
[0260] In summary, the composite coating provided by the present invention has good biocompatibility, is completely degradable, and can change the crystallization mode of the surface coating through process control to form a dense coating; even if the surface coating is damaged during use, the coating crystals that fall around it can still recrystallize and self-assemble to repair in the tissue solution, thereby continuously and effectively inhibiting the degradation of the magnesium alloy and improving the corrosion resistance of the magnesium alloy.
[0261] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a self-healing medical magnesium alloy composite coating, characterized in that: The preparation method comprises the following steps: (1) After surface treatment, the medical magnesium alloy substrate is suspended in a reaction container filled with purified water, and then sealed and subjected to a first hydrothermal reaction to obtain a bottom coating; (2) mixing the alkali solution and the calcium phosphate aqueous solution to obtain a hydrothermal reaction solution; Immersing the medical magnesium alloy substrate with the bottom coating in a hydrothermal reaction solution to perform a second hydrothermal reaction, and obtaining a surface coating after cooling; the temperature of the second hydrothermal reaction is 80-120° C.; the composition of the surface coating includes hydroxyapatite; (3) cleaning and drying the medical magnesium alloy substrate with the bottom coating and the surface coating to obtain the self-healing medical magnesium alloy composite coating; The calcium-phosphate aqueous solution includes a first calcium-phosphate aqueous solution or a second calcium-phosphate aqueous solution; The raw materials for preparing the first calcium-phosphorus aqueous solution include: calcium nitrate tetrahydrate, potassium dihydrogen phosphate, tricalcium phosphate, hydrogen peroxide, a first chelating agent and purified water; The first chelating agent includes any one or a combination of at least two of ethylenediaminetetraacetic acid disodium salt, D-anhydrous glucose or L-cysteine; The raw materials for preparing the second calcium-phosphorus aqueous solution include: calcium nitrate tetrahydrate, disodium hydrogen phosphate dodecahydrate, tricalcium phosphate, hydrogen peroxide, a second chelating agent and purified water; The second chelating agent includes D-anhydrous glucose and / or L-cysteine.
2. The preparation method according to claim 1, characterized in that: The surface treatment in step (1) includes physical grinding, cleaning and electrochemical polishing performed in sequence; In step (1), the distance between the medical magnesium alloy substrate and the surface of purified water is 15-20 mm; The temperature of the first hydrothermal reaction in step (1) is 140-200°C; The pressure of the first hydrothermal reaction in step (1) is 1.6-2.0 MPa; The time of the first hydrothermal reaction in step (1) is 2 to 5 hours.
3. The preparation method according to claim 1, characterized in that: The concentration of calcium nitrate tetrahydrate in the first calcium-phosphate aqueous solution is 20-80 g / L; The concentration of potassium dihydrogen phosphate in the first calcium phosphate aqueous solution is 5-35 g / L; The concentration of tricalcium phosphate in the first calcium-phosphate aqueous solution is 3-15 g / L; The concentration of hydrogen peroxide in the first calcium phosphate aqueous solution is 50-80 mL / L; The concentration of EDTA disodium salt in the first calcium phosphate aqueous solution is 25-50 g / L; The concentration of D-anhydrous glucose in the first calcium phosphate aqueous solution is 25-50 g / L; The concentration of L-cysteine in the first calcium-phosphate aqueous solution is 20-30 g / L; The molar ratio of calcium to phosphorus in the first calcium-phosphate aqueous solution is 1.3-1.9:
1.
4. The preparation method according to claim 3, characterized in that: The molar ratio of calcium to phosphorus in the first calcium-phosphate aqueous solution is 1.5-1.8:
1.
5. The preparation method according to claim 4, characterized in that: The molar ratio of calcium to phosphorus in the first calcium-phosphate aqueous solution is 1.6-1.7:
1.
6. The preparation method according to claim 1, characterized in that: The concentration of calcium nitrate tetrahydrate in the second calcium-phosphate aqueous solution is 10-40 g / L; The concentration of disodium hydrogen phosphate dodecahydrate in the second calcium-phosphate aqueous solution is 10-50 g / L; The concentration of tricalcium phosphate in the second calcium-phosphate aqueous solution is 10-40 g / L; The concentration of hydrogen peroxide in the second calcium phosphate aqueous solution is 50-80 mL / L; The concentration of D-anhydrous glucose in the second calcium phosphate aqueous solution is 15-20 g / L; The concentration of L-cysteine in the second calcium-phosphate aqueous solution is 20-30 g / L; The molar ratio of calcium to phosphorus in the second calcium-phosphate aqueous solution is 1.3-1.9:
1.
7. The preparation method according to claim 6, characterized in that: The molar ratio of calcium to phosphorus in the second calcium-phosphate aqueous solution is 1.5-1.8:
1.
8. The preparation method according to claim 7, characterized in that: The molar ratio of calcium to phosphorus in the second calcium-phosphate aqueous solution is 1.6-1.7:
1.
9. The preparation method according to claim 1, characterized in that: The alkali solution in step (2) includes sodium hydroxide; The pH value of the hydrothermal reaction solution in step (2) is 8-12; The pressure of the second hydrothermal reaction in step (2) is 1.0-1.5 MPa; Step (2) The second hydrothermal reaction time is 3 to 6 hours; The cleaning process in step (3) includes washing with water; The drying temperature in step (3) is 40-60°C; The drying time in step (3) is 15 to 60 minutes.
10. The preparation method according to any one of claims 1 to 9, characterized in that: The preparation method comprises the following steps: (1) The medical magnesium alloy substrate is physically polished, cleaned and electrochemically polished in sequence, and then suspended in a reaction container filled with purified water. After being sealed, a first hydrothermal reaction is performed at a temperature of 140-200° C. and a pressure of 1.6-2.0 MPa for 4-8 hours to obtain a bottom coating; The distance between the medical magnesium alloy substrate and the surface of purified water is 15-20 mm; (2) mixing sodium hydroxide and calcium phosphate aqueous solution to obtain a hydrothermal reaction solution with a pH value of 8 to 12; The medical magnesium alloy substrate with the bottom coating is immersed in a hydrothermal reaction solution at a temperature of 80 to 120° C. and a pressure of 1.0 to 1.5 MPa for a second hydrothermal reaction for 3 to 6 hours, and a surface coating is obtained after cooling; (3) washing the medical magnesium alloy substrate with the bottom coating and the surface coating with water, and then drying at a temperature of 40 to 60° C. for 15 to 60 minutes to obtain the self-healing medical magnesium alloy composite coating; The calcium-phosphate aqueous solution includes a first calcium-phosphate aqueous solution or a second calcium-phosphate aqueous solution.
11. A self-healing medical magnesium alloy composite coating, characterized in that: The self-healing medical magnesium alloy composite coating is obtained by the preparation method according to any one of claims 1 to 10; From the surface of the medical magnesium alloy substrate to the outside, the composite coating includes a bottom coating and a surface coating that are stacked.
12. The self-healing medical magnesium alloy composite coating according to claim 11, characterized in that: The bottom coating comprises magnesium hydroxide and magnesium oxide; The thickness of the bottom coating is 8-15 μm; The thickness of the composite coating is 50-80 μm.
Citation Information
Patent Citations
Preparation method of magnesium hydroxide-calcium phosphate composite coating for magnesium / magnesium alloy
CN107699885A
Magnesium alloy coating with high binding force, preparation method of magnesium alloy coating and biomedical material magnesium alloy
CN118028732A
Medical degradable magnesium alloy coating and preparation method thereof
CN118105548A
Biomedical product with a substrate comprising a nickel-titanium alloy and a coating layer comprising calcium phosphate
EP1293219A1